Spermatogonial stem cells are a promising and pluripotent cell source for regenerative medicine - Chen, Zhe (Am J Transl Res, 2020)
Regenerative medicine has been shown to hold enormous potential to treat traumatic and degenerative diseases, and substantial advancements have been made in the recent decades. In particular, different cell types were evaluated in basic research and preclinical studies on cell-based therapy applications. Despite the extraordinary achievements made in experimental studies and clinical practice, a considerable number of obstacles, such as the cellular source, ethical and safety issues, hinder further clinical applications. Spermatogonial stem cells (SSCs) are gradually becoming the research focus of cell-based regenerative medicine owing to their unique merits over other types of stem cells, particularly the lack of ethical concerns and lower immunogenicity. In addition, SSCs have been successfully induced to differentiate into other cell types under different appropriate conditions in compelling studies. Based on these properties, we systemically reviewed the development of SSCs as an attractive cell source for cell-based regenerative medicine.